Evaluation of the Physical and Chemical Properties of Vietnamese Perilla frutescens L. Essential Oil - Kim Ngan, Tran Thi; Toan, Tran Quoc; Cang, Mai Huynh (Asian Journal of Chemistry, 2020)
Perilla frutescens essential oil was studied in this work for its physico-chemical characteristics and composition. The essential oil was obtained yields by 0.1%. The physico-chemical properties of the oil were also discovered including the physico-chemical parameters averaged 0.944 g/cm3 for specific gravity, acid index (9.185 mg KOH/g), ester index (28.66 mg KOH/g), refractive index (1.4976). Thought gas chromatography/mass spectrometry (GC/MS). The results revealed that the oil is extremely rich in myristicin (43.896%), elemicin (28.793%), α-caryophyllene (8.327%), perillaldehyde (7.973%), (Z,E)-farnesene (2.807%), D-limonene (1.043%). The results showed that the morphological characteristics and the polymorphism in the essential oil composition of perilla leaves were reliant on the harvesting time and geographical cultivate. Perilla essential oil is antioxidant, antibacterial and used in many studies, helping to find its effect on Alzheimer′s disease, memory loss, concentration and anti-depressive concentration, because it contains unique compounds as above.